2021
DOI: 10.1111/chso.12487
|View full text |Cite
|
Sign up to set email alerts
|

I agreed to go because........examining the Agency of Children within a phenomenon conceptualised as trafficking in Ghana

Abstract: The legal and policy framework on child trafficking is dismissive of children's agency and regards them as vulnerable personalities. This paper examines the scope of children's agency in their transportation to other communities for fishing in Ghana. Using a phenomenological design, 17 child returnees' views were elicited on their movement for fishing activities. Findings revealed that children's agentive capabilities progressed primarily from consent giving to negotiation. Highlighting the relational and mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Furthermore, recent research in Africa has identified the agentive capacity of African children in contributing to the family production unit and other activities. These demands that African children's capabilities be taken into cognisance when developing interventions to improve childhoods on the continent (see Abebe, 2019; Abebe & Ofosu‐Kusi, 2016; Koomson et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent research in Africa has identified the agentive capacity of African children in contributing to the family production unit and other activities. These demands that African children's capabilities be taken into cognisance when developing interventions to improve childhoods on the continent (see Abebe, 2019; Abebe & Ofosu‐Kusi, 2016; Koomson et al, 2022).…”
Section: Introductionmentioning
confidence: 99%